2004
DOI: 10.5466/ijoms.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Keratocyst, Orthokeratinized Odontogenic Cyst and Epidermal Cyst: An Immunohistochemical Study Including Markers of Proliferation, Cytokeratin and Apoptosis Related Factors

Abstract: Objective: There are microscopic similarities among odontogenic keratocyst (OKC), orthokeratinized odontogenic keratocyst (DOC) and epidermal cyst (EDC). This study was to compare with cell proliferation, cell differentiation and apoptosis related factors in OKC, DOC and EDC in order to clarify the characters and category of three hitstopathologically similar cysts.Material and Methods: Fourteen cases of OKC, nine cases of DOC and eighteen cases ofEDC were examined immunohistochemically using antibodies agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
(55 reference statements)
3
18
0
Order By: Relevance
“…However, Tsuji et al (27) and Hayashi et al (28) reported that CK13 expression could not be confirmed in OOCs, being inconsistent with our present result. On the other hand, Koizumi (29) stated that CK13 was partially positive in OOCs, supporting of our result. In addition, Crivelini et al (30) described that CK13 expression in odontogenic epithelium was consistent with its expression in dental lamina.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…However, Tsuji et al (27) and Hayashi et al (28) reported that CK13 expression could not be confirmed in OOCs, being inconsistent with our present result. On the other hand, Koizumi (29) stated that CK13 was partially positive in OOCs, supporting of our result. In addition, Crivelini et al (30) described that CK13 expression in odontogenic epithelium was consistent with its expression in dental lamina.…”
Section: Discussionsupporting
confidence: 81%
“…Immunoreactivity for CK17 was found in all layers except for the basal layer in both OOCs and DCs, whereas it was partially weak but present in all layers in KCOTs, suggesting that KCOT has a more neoplastic nature. CK19 (40 kDa) is expressed in dental lamina, the enamel organ and epithelial rests of Malassez, suggesting that it may be considered an odontogenic epithelial marker (29,(33)(34)(35). In fact, several reports have indicated that CK19 is positive in the basal layer of non-keratinized epithelium, or was negative in KCOTs (25,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations